(untitled) (Journal of Guidance and Counselling Studies, 2022)
This study investigated Influence of Traffic Congestion on Psychological Stress and Pro-Social Behaviour among Commuters in Port-Harcourt Metropolis. The study adopted a descriptive-correlational research design and was guided by five research questions and four hypotheses which were tested at 0.05 level of significance. The study comprised of selected routes and fly-overs in Port Harcourt where high traffic congestion is encountered regularly. The selection of five (5) fly-overs; Rumuokoro, Waterline, Choba, Garrison and Rumuadaolu; and twenty (20) respondents were done randomly, in each of the areas making a total of 100 respondents. The researchers developed a self-reported questionnaire titled “Influence of Traffic Congestion on Psychological Stress and Pro-Social Behaviour (ITCPSPB)”, to gather data from commuters. The simple percentage descriptive statistics was used to answer research question one and Pearson Product Moment correlation statistics was used for data analysis using the SPSS 22 version, to answer question two to five. Results revealed that commuters experience significantly high traffic congestion in Port Harcourt metropolis. Findings from the study further revealed a significant relationship between components of psychological stress (frustration, fatigue, and anger outburst), pro-social driving behaviour and traffic congestion among commuters in Port Harcourt Metropolis. Based on these findings, it was recommended that proper orientation and re-orientation programme for road users on effective utilization of the road should be organized regularly by relevant agencies, markets, malls, and shops should be cited few kilometers away from busy roads and junctions to reduce illegal parking and pedestrian movement. Policy makers should initiate the provision of well-equipped quick traffic response unit to deal with frequent vehicle breakdowns on the road to allow easy flow of traffic always.